2015
DOI: 10.1002/berj.3194
|View full text |Cite
|
Sign up to set email alerts
|

Studying while doing time: understanding inmates’ conceptions of learning

Abstract: Low levels of education and dropping out of school are associated with criminal involvement. The Portuguese prison system, similar to other prison systems (e.g. England), offers prison-based educational programmes so inmates can complete compulsory education. However, the completion rate of these educational programmes is low, and the dropout rate is high. Deepening our understanding of how inmates conceptualise learning and how they engage in learning will improve the quality of the prison-based educational s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…As there are numerous positive outcomes related to participation in education during a detention period (e.g., decreasing recividism, Kim & Clark, 2013;transforming lives, Behan, 2014;Stern, 2013; retaining a sense of agency within the controlled and coercive prison environment, Behan, 2014; creating a regime of dynamic security, Costelloe & Langelid, 2011), it is important to explore the educational opportunities for FNPs. However, the majority of the academic research about prison education focuses only on national prisoners (e.g., Rosário et al, 2016;Roth & Manger, 2014). Thus, the question remains whether FNPs have the same opportunity to learn as prisoners detained in their own countries.…”
Section: Discussionmentioning
confidence: 99%
“…As there are numerous positive outcomes related to participation in education during a detention period (e.g., decreasing recividism, Kim & Clark, 2013;transforming lives, Behan, 2014;Stern, 2013; retaining a sense of agency within the controlled and coercive prison environment, Behan, 2014; creating a regime of dynamic security, Costelloe & Langelid, 2011), it is important to explore the educational opportunities for FNPs. However, the majority of the academic research about prison education focuses only on national prisoners (e.g., Rosário et al, 2016;Roth & Manger, 2014). Thus, the question remains whether FNPs have the same opportunity to learn as prisoners detained in their own countries.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, according to Rosario et al (2016) learning is described by inmate students as a means to acquire knowledge and competencies with practical applicability, thereby preparing them for life outside of Correction, and more immediately, helping them in the daily tasks and issues they face in Correction. In Norway the study showed that the Correction inmates are generally quite satisfied with the education quality, that they are highly motivated, and use appropriate learning strategies (Diseth et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Duwe and Clark (2014) found that, obtaining a secondary degree in Correction significantly increased the odds of securing post-release employment. Thus, Rosario et al (2016) noted that Correction educators must support prisoners who enroll in learning activities and prevent early drop out by designing new and creative Correction-based educational programmes.…”
Section: Introductionmentioning
confidence: 99%